Tranformasi PDI Perjuangan dari Oposisi ke Kekuasaan: Kepemimpinan dan Strategi dalam Sistem Multipartai Indonesia 1999-2004 - Danu Prasetyo; Endang Sulastri (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study examines the political transformation of the Indonesian Democratic Party of Struggle (PDI Perjuangan) from opposition to governing party during 1999–2004. Using a qualitative case study approach, this research explores the interaction between internal factors including Marhaenism ideology, Megawati Soekarnoputri's leadership, and party organizational institutionalization and external factors comprising fragmented multiparty system and post-reform coalition dynamics. The findings reveal that PDI Perjuangan's transformation was a multidimensional and dialectical process: the party's spectacular 33.74% electoral victory in the 1999 election did not automatically translate into executive power due to the political blockade by the Central Axis (Poros Tengah) coalition in the People's Consultative Assembly. This failure became a catalyst for strengthening internal institutionalization through grassroots consolidation, ideological revitalization, and systematic cadre development via the Party School. Megawati's leadership functioned as a unifying nexus integrating ideological, institutional, and coalition-building capacities. The successful transformation in 2001 reflects the party's ability to balance ideological steadfastness with strategic flexibility within an unconsolidated multiparty system.